LQR Optimal Control Applied in an Energy Harvesting System with Non-ideal Excitation Operating with Uncertain Parameters - de Almeida, Estevão Fuzaro [UNESP]; Chavarette, Fábio Roberto [UNESP] (Springer Nature, 2022)
The majority of active control applications in vibrational dynamic systems are utilized to minimize vibrations. The goal of this research, on the other hand, is to employ vibrations to generate electrical energy in such a way that the vibration becomes a desired phenomenon. The change of the physical characteristics of the system was conducted in this work with the goal of enhancing the modeling of complex energy harvesting systems with non-ideal excitation, bringing higher resilience, and bringing them closer to reality. To stabilize the orbits and compare the power generated by the systems with and without control, the optimal control technique via Linear Quadratic Regulator (LQR) is used.
Keywords: Energy harvesting; Linear quadratic regulator (LQR); Non-ideal excitation; Optimal control; Uncertain parameters